Simulation on the Use of LOSAT Data for Rice Field Mapping - Trisasongko, Bambang H.; Panuju, Dyah R; Tjahjono, Boedi; Barus, Baba; Wijayanto, Hari; Raimadoya, Mahmud A.; Irzaman, Irzaman (Makara Journal of Technology, 2010)
Simulation on the Use of LOSAT Data for Rice Field Mapping. Since the launch of LAPAN-TUBSAT satellite in 2007, Indonesia has been developing mission on earth observation missions for various applications. The next generation mission, called LAPAN-ORARI Satellite (LOSAT), is currently under development and expected to be launched in 2011. In order to facilitate the applications, a thorough assessment of the sensor should be made. This paper presents an examination of simulated LOSAT data for rice monitoring and mapping purposes coupled with QUEST statistical tree. We found that three-band simulated LOSAT data were suitable for the task with reasonably high accuracy.